2015
DOI: 10.1088/0004-637x/813/1/59
|View full text |Cite
|
Sign up to set email alerts
|

Observational Evidence of Electron-Driven Evaporation in Two Solar Flares

Abstract: We have explored the relationship between hard X-ray (HXR) emissions and Doppler velocities caused by the chromospheric evaporation in two X1.6 class solar flares on 2014 September 10 and October 22, respectively. Both events display double ribbons and Interface Region Imaging Spectrograph (IRIS) slit is fixed on one of their ribbons from the flare onset. The explosive evaporations are detected in these two flares. The coronal line of Fe XXI 1354.09Å shows blue shifts, but chromospheric line of C I 1354.29Å sh… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
60
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 52 publications
(69 citation statements)
references
References 87 publications
(139 reference statements)
8
60
1
Order By: Relevance
“…A delay of >60 s between the starting times of condensation and evaporation has been observed Young et al 2015). Both the upward evaporation velocities and downward condensation velocities are positively correlated with the HXR fluxes, which is consistent with the numerical model of evaporation driven by nonthermal electrons Li et al 2015a). …”
Section: Introductionsupporting
confidence: 81%
See 1 more Smart Citation
“…A delay of >60 s between the starting times of condensation and evaporation has been observed Young et al 2015). Both the upward evaporation velocities and downward condensation velocities are positively correlated with the HXR fluxes, which is consistent with the numerical model of evaporation driven by nonthermal electrons Li et al 2015a). …”
Section: Introductionsupporting
confidence: 81%
“…Ichimoto & Kurokawa (1984) studied Czaykowska et al (1999) found that the Fe xvi downward velocity of the regions between the flare ribbons and the magnetic neutral line decreases from ∼90 km s −1 to ∼15 km s −1 within 2.5 minutes in the gradual phase, indicating ongoing magnetic reconnection. Li et al 2015a;Tian et al 2015;. However, it can reach ∼20 minutes in an M1.0 flare ).…”
Section: Introductionmentioning
confidence: 98%
“…Blueshifts (redshifts) caused by chromospheric evaporation (condensation) have been reported in a large number of studies; see for example, blueshifted components with velocities of 200-400 km s −1 in the Ca XIX 3.18Åline (Antonucci et al 1982(Antonucci et al , 1985Antonucci & Dennis 1983;Zarro & Lemen 1988;Wülser et al 1994;Ding et al 1996) from the Bent and Bragg Crystal Spectrometer (BCS; Acton et al 1980) on board the Solar Maximum Mission and Yohkoh/BCS (Culhane et al 1991), blueshifts of 60-300 km s −1 in the Fe XIX 592.23Åline (Teriaca et al 2003(Teriaca et al , 2006Del Zanna et al 2006;Brosius & Phillips 2004) from the Coronal Diagnostic Spectrometer (Harrison et al 1995) Wülser et al 1994;Ding et al 1995;Czaykowska et al 1999;Brosius 2003;Teriaca et al 2003Teriaca et al , 2006Kamio et al 2005;Del Zanna et al 2006). In particular, blueshifts and redshifts can appear at a given flaring location in different emission lines, as observed by Hinode/EIS (Milligan & Dennis 2009;Chen & Ding 2010;Li & Ding 2011;Doschek et al 2013) (Tian et al 2014Battaglia et al 2015;Brosius & Daw 2015;Graham & Cauzzi 2015;Li et al 2015aLi et al , 2015bPolito et al 2015Polito et al , 2016Sadykov et al 2015Sadykov et al , 2016Young et al 2015;…”
Section: Introductionmentioning
confidence: 79%
“…DISCUSSION Chromospheric evaporation has been extensively studied in the past three decades. The temperatures of evaporation upflows can reach tens of millions degrees (e.g., Young et al 2013;Tian et al 2014;Li et al 2015;Polito et al 2015;Zhang et al 2016a). In this study, the converging motion from the footpoints to the loop top and filling process in the flare loop are simultaneously observed by SDO/AIA in 131Å and the SXR filters on board XRT.…”
Section: Chromospheric Evaporationmentioning
confidence: 99%